Dispersal of juvenile collared lemmings ( Dicrostonyx groenlandicus ) in a high-density population - Blackburn, Gwylim S; Wilson, Deborah J; Krebs, Charles J (Canadian Journal of Zoology, 1998)
We tested whether dispersal of juvenile lemmings occurs at high population densities and whether predation risk affects movements of juveniles. The study was conducted in July and August 1996 on the Kent Peninsula, Northwest Territories, during a peak in the lemming cycle. We fitted 43 juvenile collared lemmings (Dicrostonyx groenlandicus) of the summer generations on a control plot and a predator-exclosure plot with radio transmitters and examined their home ranges and movement patterns. We tested the following hypotheses: (i) extensive juvenile dispersal will occur at high population densities, (ii) male juveniles will move greater distances than females, and (iii) juveniles will move greater distances in the absence of predators. We rejected all these hypotheses. All juvenile collared lemmings remained in the vicinity of their original home ranges. Home-range sizes of all juveniles were similar, the mean size being 100 m 2 . Mean and maximum distances moved were similar among all juveniles. However, juveniles moved less frequently on the control plot than on the exclosure plot. Juvenile collared lemmings do not disperse at high densities. The lack of dispersal may have been the result of avoidance of confrontations with other lemmings, and may also have been related to delayed breeding, since most juveniles and subadults did not mature in late summer. Differential predation risk or predation mortality may have had no effect on the distances moved by juveniles or may have been masked by strong density effects on both plots.